Oxytocin Receptor (OXTR) Polymorphisms and Attachment in Human Infants - Chen, Frances S.; Barth, Maria; Johnson, Stephen L.; Gotlib, Ian H.; Johnson, Susan C. (Frontiers in Psychology, 2011)
Ordinary variations in human infants’ attachment behaviors—their proclivity to seek and accept comfort from caregivers—are associated with a wide range of individual differences in psychological functioning in adults. The current investigation examined variation in the oxytocin receptor (OXTR) gene as one possible source of these variations in infant attachment. One hundred and seventy-six infants (77 Caucasian, 99 non-Caucasian) were classified as securely or insecurely attached based on their behavior in the Strange Situation (Ainsworth et al., 1976). The A allele at OXTR rs2254298 was associated with attachment security in the non-Caucasian infants (p < .005). These findings underscore the importance of oxytocin in the development of human social behavior and support its role in social stress-regulation and the development of trust.